CHARACTERISTIC FEATURES OF LANGUAGE AND CULTURE IN THE FIELD OF TRANSLATION - Shoxobiddinov Sirojiddin Isomiddin o’g’li (Galaxy International Interdisciplinary Research Journal, 2022)
The purpose of the article is to illustrate the characteristics of language and culture in translation. Moreover, it demonstrates some characteristics and peculiarities of translating language.